Meningkatkan motivasi belajar siswa pada materi perdagangan internasional melalui model Make A Match di kelas IX C SMP Lab UM - Yudha Intan Kartika Buana; Agus Purnomo (Universitas Negeri Malang, 2019)
Motivation is identified as one of the important factors in constructing knowledge. This process is a vital part of constructivism learning. The purpose of this article is to examine the motivational strength of its application in Classroom Action Research (CAR). The results show that there is very little attention in motivation. In fact, if educators can increase motivation it will have an impact on the construction stage of knowledge in students. Therefore there are at least 3 components that need to be considered related to motivation in constructivism learning, namely: (1) learning challenges, (2) dual goals, and (3) class climate.DOI: 10.17977/um022v4i12019p001